Selective Use of Modern Cementless Total Knee Arthroplasty is Not Associated with Increased Risk of Revision in Patients Aged 65 or Greater: An Analysis from the American Joint Replacement Registry - Kagan, Ryland; Pelt, Christopher E.; Khanuja, Harpal S.; Oni, Julius K.; Zaniletti, Isabella; De, Ayushmita; Hegde, Vishal (The Journal of Knee Surgery, 2024)
Modern highly porous surfaces have increased confidence and use of cementless total knee arthroplasty (TKA) in the United States. As cementless TKA use increases, there remains a paucity of literature regarding associated risk of revision in patients aged ≥65 years. We analyzed the American Joint Replacement Registry (AJRR) data from January 2012 to March 2020 identifying patients aged ≥65 years undergoing primary TKA with linked cases to supplemental centers for Medicare and Medicaid data. Patients with hybrid fixation, reverse hybrid fixation, missing component data, highly constrained implants, and stem extension/augmentation were excluded. We identified 442,745 cemented TKAs and 19,841 modern cementless TKAs with a minimum of 2-year follow-up. Cumulative incident function (CIF) curves and cause-specific Cox models evaluated the risk of all-cause revision and revision for mechanical loosening, adjusting for body mass index (BMI), sex, age, cruciate retaining (CR) versus posterior stabilized (PS) femoral design, patellar resurfacing, and Charlson's comorbidity index (CCI). Patients with cementless compared with cemented TKA were younger (mean age: 71.9 vs. 73.2 years, p < 0.001), more likely to be male sex (48.8 vs. 39.0%, p < 0.001), more likely to have a CR femoral design (81.1 vs. 45.7%, p < 0.001), less likely to have patellar resurfacing (92.7 vs. 95.0%, p < 0.001), and had a lower CCI (mean: 2.9 vs. 3.1, p < 0.001). Adjusted hazard ratios (HRs) showed no difference in associated risk for all-cause revision (HR: 1.07; 95% confidence interval [CI]: 0.92–1.24; p = 0.382) or revision for mechanical loosening (HR: 1.38; 95% CI: 0.9–2.12; p = 0.14) for cementless versus cemented TKA. Our results suggest that current selective use of cementless fixation for TKA in patients aged ≥65 years in the United States is not associated with an increased risk of revision. While encouraging, further study is necessary to establish indications for use in this age group prior to broader adoption in this patient population.Level of Evidence Therapeutic Level III.
Keywords: total knee arthroplasty; American Joint Replacement Registry; cementless total knee; registry